The Impact of Debt Rating Mediation on ESG Scores and Corporate Debt Costs in Indonesia for the Period 2018 - 2023 - Rifqi Satria Dinandra; Zuliani Dalimunthe (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the impact of debt rating mediation on ESG scores and corporate debt costs in Indonesia for the period 2018 – 2023. This research falls under quantitative research with data collection consisting of secondary data available to the public (Indonesia Stock Exchange) and Refinitiv. The type of data used is cross-sectional data. The sample in this study comprises 235 bond data points from 22 companies listed on the Indonesia Stock Exchange, issued between 2018 and 2023. The type of data used is cross-sectional data. The research findings indicate that ESG score performance, debt ratings, state-owned enterprise status, and decarbonization acceleration regulations influence corporate debt costs. Additionally, debt ratings fully mediate the relationship between ESG scores and corporate debt costs.